Optimization of Injection Molding Temperature and Pressure on the Quality of Polypropylene Cutting Board - Sugeng Hadi Susilo; Ramadhana Luhur Prabangkara (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
This study delves into the optimization of polypropylene cutting board production through injection molding. Polypropylene, derived from propylene monomers, serves as the primary material. The injection molding process often leads to flash defects due to inadequate temperature and pressure settings. The research aims to discern the individual and interactive effects of temperature and injection pressure on the weight and surface area of the cutting boards. Experimental variations encompass temperature levels of 165°C to 175°C and injection pressures ranging from 25 Psi to 35 Psi. Data collection employs experimental methods, and analysis utilizes factorial and RSM approaches. Findings reveal that the lightest cutting boards result from the lowest temperature (165°C) and injection pressure (25 Psi), with an average weight of 105.6009 grams and a surface area of 21,158.3333 mm². In conclusion, both temperature and injection pressure significantly influence the weight and surface area of polypropylene cutting boards, providing valuable insights for enhanced manufacturing processes.